Biallelic pathogenic variants in POLR3D alter tRNA transcription and cause a hypomyelinating leukodystrophy: A case report - Macintosh, Julia; Perrier, Stefanie; Pinard, Maxime; Tran, Luan T.; Guerrero, Kether; Prasad, Chitra; Prasad, Asuri N.; Pastinen, Tomi; Thiffault, Isabelle; Coulombe, Benoit; Bernard, Geneviève (Frontiers in Neurology, 2023)
RNA polymerase III-related leukodystrophy is a rare, genetic form of pediatric neurodegeneration characterized by an insufficiency of myelin deposition in development. While one of the most common forms of hypomyelinating leukodystrophy, a subset of individuals with clinically diagnosed POLR3-related leukodystrophy remain without a genetic diagnosis. Here, we demonstrate the first case of POLR3-related leukodystrophy caused by biallelic pathogenic variants in POLR3D, a missense variant (c.541C>T, p.P181S) and an intronic splice site variant (c.656-6G>A). The individual described had an MRI distinguishable for diffuse hypomyelination yet myelin preservation in structures characteristically spared in POLR3-related leukodystrophy and demonstrated canonical neurological and non-neurological features, including cerebellar involvement (e.g., ataxia, dysarthria, intention tremor) for the former and hypodontia and hypogonadotropic hypogonadism for the latter. Functional studies were pursued and revealed decreased expression of POLR3D at the RNA level and aberrant expression of RNA polymerase III transcripts, most notably at the level of tRNA genes. Additionally, the p.P181S missense variant was shown to impact the interaction of Pol III with its chaperone complex, the PAQosome. In sum, this work identifies POLR3D as a novel gene associated with disease and expands the genetic spectrum of RNA polymerase III-related leukodystrophy.